Distinctions regarding practical philosophy. Indirect conceptual questions to discursive ethics - Kambartel, Friedrich; Cortés Rodas, Francisco (Estudios de Filosofía, 1996)
This article is a critique on the discursive ethics of Habermas, according to which a theory of discourse based on the rational consent is not a proper foundation for understanding moral philosophy. The author sets forth another perspective to define the frame of morality. For him, morality is related lo our basic conditions of corporeity and rationality. Then, the moral intend would be to protect those basic necessities to a worthy human life.